2018
DOI: 10.1097/igc.0000000000001266
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Assessment of Urologic Procedures and Operations After Surgery or Pelvic Radiation for Cervical Cancer

Abstract: Women treated for cervical cancer undergo ureteral stricture interventions at 0.8% per year over the 20 years after their treatment; this risk is higher among women who receive radiation treatment. Fistula repair is rare after cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(21 reference statements)
0
6
0
2
Order By: Relevance
“…After gynecologic oncology treatment (radiotherapy/surgery ± chemotherapy), approximately 40% of patients have gastrointestinal reactions that affect quality of life [36]. Some patients even need surgery to treat urinary tract injury (surgery vs. radiotherapy: 6.3% vs 11.2%) [37]. Our study showed that the NACT+S group appeared to have an advantage in cumulative toxicity compared to the CCRT group.…”
Section: Discussionmentioning
confidence: 78%
“…After gynecologic oncology treatment (radiotherapy/surgery ± chemotherapy), approximately 40% of patients have gastrointestinal reactions that affect quality of life [36]. Some patients even need surgery to treat urinary tract injury (surgery vs. radiotherapy: 6.3% vs 11.2%) [37]. Our study showed that the NACT+S group appeared to have an advantage in cumulative toxicity compared to the CCRT group.…”
Section: Discussionmentioning
confidence: 78%
“…Therefore, ureteral stricture often occurs in the middle and lower part of the ureter after radiotherapy. Welk et al [ 18 ] retrospectively analyzed a Canadian database of adult cervical cancer patients from 1994 to 2014, and found that the incidence of ureteral stricture after radiotherapy was 16%, which was higher than the surgery and radiation group (11%) and surgery alone group (5%). Elliott et al [ 19 ] also reported that the incidence of ureteral stricture in cervical cancer patients treated with radiotherapy after radical resection was lower than that of patients treated with radiotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from bevacizumab, other risk factors for fistulas include radiotherapy (rectal dose ≥ 76 Gy), previous surgery, tumor stage (III or IV vs. I or II), ureteral stents, nutritional status and inflammatory bowel disease [19,[22][23][24][25][26]. In the present study, all patients who developed a fistula had undergone previous radiotherapy, which was also the case for all the patients who developed grade 3 fistula in the final analysis of the GOG 240 study [12].…”
Section: Discussionmentioning
confidence: 99%